Non-ohmic properties of CaCu3Ti4O12 thin films deposited By RF-sputtering - Foschini, C. R. [UNESP]; Hangai, B. [UNESP]; Cavalcante, C. S. [UNESP]; Simões, A. Z. [UNESP]; Cilense, M. [UNESP]; Longo, E. [UNESP] (Springer Nature, 2017)
Calcium copper titanate (CaCu3Ti4O12, CCTO), thin films with polycrystalline nature have been deposited by RF sputtering on Pt/Ti/SiO2/Si (100) substrates at a room temperature followed by annealing at 600 °C for 2 h in a conventional furnace. The CCTO thin film present a cubic structure with lattice parameter a = 7.379 ± 0.001 Å free of secondary phases. Dielectric spectroscopy was employed to examine the polycrystalline behaviour of CCTO material and the mechanisms responsible for the barrier-layer capacitances associated with Schottky-type barriers and the non-Ohmic properties. The film presents an electric breakdown field (Eb = 203 V cm−1) and then nonlinear coefficient (α = 6), which is even lower than that of the ZnO and SnO2 based varistors The observed electrical features of CCTO thin films are highly dependent on the [CaO12], [CaO4], [CuO11], [CuO11Vo x] and [TiO5·VO∙] clusters.